Case Report: Simultaneous Presence of Primary and Permanent Teeth - Fatemeh Jahanimoghadam; Reihaneh Hosseinifar (Negah Institute for Scientific Communication, 2015)
Although the delayed exfoliation of primary teeth among children is a common dental problem, simultaneous presence of primary teeth and corresponding successors is a rare feature in adults. This paper reports an unusual case in which both permanent teeth (molars, premolars, and canines) and primary teeth were present simultaneously. This report describes questions concerning the etiology of overretention of primary teeth.